Endothelial cell metabolism and implications for cancer therapy. - Harjes, U; Bensaad, K; Harris, A (2012)
Tumour tissue is characterised by fluctuating oxygen concentrations, decreased nutrient supply, and acidic pH. The primarily glycolytic metabolism of tumour cells contributes to this, with increased glucose consumption and increased lactate secretion. Endothelial cells are particularly challenged when recruited towards the tumour metabolic environment. They are required to proliferate and form functional networks in order to establish continuous blood flow. Considering that deregulated metabolism is an emerging hallmark of cancer and target of tumour therapy, it is of importance to incorporate the current knowledge about how the tumour metabolic environment, as a therapy target, can affect endothelial cell metabolism and the angiogenic response. Recent studies have shown differences in metabolic pathways in endothelial cells compared with other normal or tumour tissues. Therefore, we have reviewed relevant literature on endothelial metabolism and the response to angiogenic activation in conditions of metabolic stress.